The Relationship between Parental Support and Personal Hygiene Behavior during Menstruation in Early Adolescent Girls - Maysaroh Nuril Hasanah; Irwina Angelia Silvanasari (LPPM Universitas dr. Soebandi, 2026)
Introduction: The reality is that many young adolescent girls still have poor personal hygiene practices. Parental support is crucial in shaping personal hygiene practices in adolescents who are just starting to menstruate. The purpose of this study was to analyze the relationship between parental support and personal hygiene practices during menstruation in young adolescent girls. Methods: This study was designed using a correlational approach with a cross-sectional approach. The population was 32 fifth and sixth grade female students at SDN 1 Lamongan, with a total sample of 32 students drawn from total sampling. The independent variable was parental support, and personal hygiene practices served as the dependent variable. The instruments used in this study were a questionnaire on personal hygiene practices and parental support, which has been validated and reliable. The analysis used frequency distributions for categorical data and assessed the mean, median, and standard deviation for numerical data. Bivariate analysis was conducted to test the relationship between the two variables using the gamma test. Results: Most respondents (22) (86.8%) received moderate parental support, and most respondents (21) (65.6%) had adequate levels of support. The gamma test results showed a p-value (0.001) <α (0.05), thus accepting the hypothesis that there is a significant relationship between parental support and personal hygiene behavior. Conclusions: There is a relationship between parental support and personal hygiene behavior during menstruation in early adolescent girls. High parental support tends to improve personal hygiene behavior. Early adolescent girls should practice good personal hygiene behavior during menstruation. Parents should provide support through open communication, accurate and clear information, menstrual products, and positive praise.